2019
DOI: 10.1212/wnl.0000000000007786
|View full text |Cite
|
Sign up to set email alerts
|

STXBP1encephalopathy

Abstract: De novo pathogenic variants in STXBP1 encoding syntaxin1-binding protein (STXBP1, also known as Munc18-1) lead to a range of early-onset neurocognitive conditions, most commonly early infantile epileptic encephalopathy type 4 (EIEE4, also called STXBP1 encephalopathy), a severe form of epilepsy associated with developmental delay/intellectual disability. Other neurologic features include autism spectrum disorder and movement disorders. The progression of neurologic symptoms has been reported in a few older aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 66 publications
2
14
0
1
Order By: Relevance
“…4 B). Inspection of the peptides clustering within each factor suggests that each factor may represent a distinct biological function (Supplementary Table 3 ) for example cell structure integrity 12 14 , synaptic plasticity 15 20 , mitochondrial bioenergetics, signal transduction and cell proliferation 4 , 21 27 and amyloid 28 .…”
Section: Discussionmentioning
confidence: 99%
“…4 B). Inspection of the peptides clustering within each factor suggests that each factor may represent a distinct biological function (Supplementary Table 3 ) for example cell structure integrity 12 14 , synaptic plasticity 15 20 , mitochondrial bioenergetics, signal transduction and cell proliferation 4 , 21 27 and amyloid 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A misfolded protein that is prone to degradation and aggregation may also destabilize and co‐aggregate the proteins it is directly bound to. Interestingly, co‐aggregation of mutant STXBP1 with alpha‐synuclein has been proposed (Chai et al 2016), which may explain the Parkinsonian symptoms seen in some older patients (Lanoue et al 2019). It remains to be seen whether this effect is also present in other types of mutations in which part of the protein, presumably containing the motif that is responsible for binding of STXBP1 to its interactors, remains intact.…”
Section: Disease‐causing Mutations In Stxbp1mentioning
confidence: 99%
“…In fact, de novo mutations in STXBP1 are among the most frequent causes of epilepsies and encephalopathies with most patients also having severe to profound intellectual disability and movement disorders (Stamberger et al., 2016). More than 85 pathological STXBP1 variants are reported, with little genotypic‐phenotypic correlation (Lanoue et al., 2019). This suggested that pathology primarily arises from a loss of function and STXBP1 haploinsufficiency (Yamamoto et al., 2016).…”
Section: Disruption Of Sv Primingmentioning
confidence: 99%
“…Furthermore, expression of human mutants in Stxbp1 heterozygous neurons results in greatly reduced total munc‐18 levels, exceeding that expected from loss of mutant protein alone (Chai, Sierecki, & Tomatis, 2016; Guiberson et al., 2018; Kovačević et al., 2018; Patzke et al., 2015). This is proposed to reflect a gain of function pathology that is associated with an aggregation of STXBP1 mutants with remaining wild‐type protein (Lanoue et al., 2019). When common pathological STXBP1 variants were expressed in either Stxbp1 knockout mouse neurons or were added to an in vitro fusion assay, impaired neurotransmission or defective SNARE‐dependent membrane fusion were respectively observed (Guiberson et al., 2018; Kovačević et al., 2018; Shen et al., 2015).…”
Section: Disruption Of Sv Primingmentioning
confidence: 99%